ASSEMBLY elections 2002: under the shadow of fear (2002)
The Jammu and Kashmir elections held in four phases between the months of September and October faced the constant threat of disruption from militant attacks. However, as this report based on a teamwide study conduced by the ISS across 14 districtsw reveals, the elections threw up a few welcome surprises. - Reproduced.
Keywords: Jammu and Kashmir. Legislative Assembly - Elections; Elections